HUBUNGAN KECEPATAN DAN KOORDINASI MATA DAN KAKI DENGAN KEMAMPUAN DRIBBEL PADA PEMAIN SEPAKBOLA OSOSBER FC - Pranata, Ardi; Zainur, Zainur; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: based on the author's observations and also information from the coaches, that the player Ososber FC which follow the practice does not yet have a good dribble ability, whether exercise or in the match. This is clearly visible at the time of exercise they did dribble too the eyes focus on the obstacles, so the ball is difficult to control and easy to lose the ball, and then the ball too far away from the legs, seen that coordination is one of the the cause of the low heel. The goal in this is to research the information relationship between speed and the coordination of the eyes and feet with the ability to dribble the ball players in the study Population Ososber FC seluru FC Ososber players who follow the exercises amounted to 17 people. The sample in this study less than a hundred then samples taken (total sampling) or sampling technique in full Ososber FC players that add up to 17 people. Instruments in this research in the form of tests including speed tests by using the test run 30 meters, test the coordination of eye and foot danTes dribble by dribble. Based on the results of research that has been the author of the previous chapters describe, then it can be taken to the following conclusion: there is a relationship between the speed with the ability to dribble the ball, where significant extent on Î± rtab (0.05) = 0.497 means rhitung (0.736) > rtab (0.497). Then there is the relationship between the coordination of the eyes and feet with the ability to dribble the ball, where significant extent on Î± rtab (0.05) = 0.497, meaning rhitung (0.553) > rtab (0.497) and there is a relationship together between the speed and coordination of the eyes and walk with the ability to dribble the ball player Ososber FC, where significant extent on Î± rtab (0.05) = 0.497, meaning Rhitung (0.753) > rtab (0.497).Key Words: Speed, coordination of the eyes and feet, Dribble the ball Ability